A systematic review on the association between obstructive sleep apnea and chronic kidney disease. (October 2020) - Umbro, Ilaria; Fabiani, Valerio; Fabiani, Mario; Angelico, Francesco; Del Ben, Maria
Summary: This systematic review aims to provide a more comprehensive overview of the association between obstructive sleep apnea (OSA) and chronic kidney disease (CKD). A PubMed search was conducted using the terms "(obstructive sleep disorders OR obstructive sleep apnea OR obstructive sleep apnea syndrome) AND (kidney function OR renal outcome OR chronic kidney disease OR end stage renal disease)". Four hundred seventy four articles were initially retrieved, 227 in the last five years. We included articles with similar definitions of OSA, in particular only diagnosed by polysomnography, in order to exclude bias related to different diagnostic clinical tools, prediction algorithms and questionnaires that affected previous studies. Six cross-sectional and two retrospective studies were analyzed. There were a total of 8795 participants across all the studies with a mean age between 51 and 63 years. One study included only males but the proportion of males in the other studies ranged from 58 to 85.6%. The mean body mass index ranged from 25.2 to 32 kg/m 2 . The majority of studies considered indicate that OSA and CKD are significantly associated, in particular in their more severe categories. It is of great importance to set up a strong clinical collaboration between sleep medicine and nephrology.